Palay, policy and public administration the Masagana 99 program revisited - Smith, Kenneth P. (1989)
During the period 1973 to 1977, the management of 'Masagana 99" -- the national rice production program of the Marcos Administration -- under the direction of Agriculture Secretary (later Minister) Arturo Tanco Jr. was significantly different from the management of any previous Philippine agricultural program. The problems of program management were consciously addressed by Tanco in Masagana to a degree never before undertaken. A rationally-structured control-type Management Information System (MIS) was one of the principal administrative management techniques employed by the then Secretary which contributed to the success of the early Masagana program. Using the data amassed by that Management Information System. together with information from other sources, the Masagana program was reviewed to reevaluate both its achievements, and the appropriateness of its primary policy assumptions. From this review, several startling conclusions were reached which have major implications for both the design and the administration of future agricultural production programs.
Keywords: Masagana 99 (Rice Production Program); Rice -- Production; Rice industry